PINOYLISH: THE AWARENESS AND NOTIONS OF UNIVERSITY STUDENTS IN NORTHERN LUZON - Quinto, Joseph Bello (TEFLIN Journal, 2024)
Pinoylish (Philippine English) has made a mark in the literature, although research on the perspectives of university students on Pinoylish is still scarce. As a result, a sequential explanatory mixed-methods design was undertaken to investigate the awareness and notions of 761 university students in Northern Luzon, Philippines. The results revealed that university students were not oblivious; however, they were marginally aware of the meanings, features, and uses of Pinoylish, implying that they do not possess a complete understanding of this variety of English. This study also unveiled that university students disagreed on negative notions while agreeing on positive notions of Pinoylish; this consensus can be interpreted as a positive attitude toward Pinoylish. Drawing on the findings, this study has implications for the pluricentric model of English Language Teaching (ELT) and suggests possible research trajectories.